Modelling of the effects of fluid substitution in the visean deposits of the Yablunivske field based on the interpretation of well logging data and petrophysics - Yemets, V.; Bezrodna, І.; Antoniuk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
he paper discusses the details of the application of the method of fluid substitution which is used for predicting elastic properties of reservoir rocks and their dependence on pore fluid and porosity. This method makes it possible to predict changes in elastic response of a rock saturation with different fluids. The main task of this paper was to study the productive zones of the visean deposits of the Yablunivske field using the example of a single well. The integration of petrophysics and rock physics (Gassmann fluid substitution) was applied to sandstones with intergranular porosity. The objective of the study was to use petrophysical dependences, cross-plots and Gassmann fluid substitution modelling to determine the effect of different pore fluids (brine, oil, gas) on acoustic properties (compressional velocity, shear velocity, density). It was established that the sandstone is a predominant type of reservoir of the considered rocks. The effect of fluid substitution on elastic properties was determined as a result of the implementation of Gasman's technique. The compressional velocity and density decreased, shear velocity slightly increased when brine was substituted with gas for the formed models. Limit values of acoustic impedance and Vp/Vs have been established for the water saturated and hydrocarbon saturated strata of the V-20 – V-22 horizons. It can be used for the drilling new wells of the Yablunivske field creating elastic reservoir rock models.
Keywords: petrophysics; rock physics; well logging; Gassmann fluid substitution; visean deposits